Microstructure, matrix interactions, and molecular structure are the key determinants of inherent glycemic potential in pearl millet (Pennisetum glaucum). (June 2022) - Mondal, Debarati; Awana, Monika; Aggarwal, Shilpi; Das, Debarup; Thomas, Bejoy; Singh, S.P.; Satyavathi C, Tara; Sundaram, Raman M.; Anand, Anjali; Singh, Archana; Sachdev, Archana; Praveen, Shelly; et al.
Abstract: The archaeological staple, pearl millet (PM) has been acclaimed to be slow digestible with ultimate lower inherent glycemic potential (IGP) among the staple cereals. IGP which directly depends on the rate and extent of starch hydrolysis, also depends on various intrinsic variables like food microstructure, food matrix composition/component interactions as well as the molecular configuration of starch. As comprehensive characterization of inherent variables of IGP was largely ignored, the present work aimed to investigate that in PM. In-vitro oro-gastro intestinal simulation revealed PM to be low IGP (63.71%) compared to rice (65.89%). Microstructural analysis revealed that high pericarp thickness (22.71 ± 0.20 μm) could be a vital component hindering the easy accessibility of carbolytic enzymes even though granule size (2.16 ± 0.12 μm), as well as endodermal surface area (1199.64 ± 2.86 μm 2 ), was lower than control rice. It was also found that dense food matrix components and higher starch-lipid (S-L) interaction visualized by CLSM contributes to the resistance towards digestive enzymes. The molecular structures were explored using FTIR, XRD to understand the synergistic effects of short-range and longer-range molecular patterns (R1047/1022 : 0.80 & CD %: 21.73%) of PM starch, which revealed the superior crystalline compactness as vital towards low IGP. The results show the importance of microstructure, dense composition, molecular configuration of starch as well as component interactions (S-L) in attenuating starch digestion in a real food matrix ( i.e. PM) while the complexities of real digestion should be considered and explored using dynamic models in future. Graphical abstract: Image 1 Highlights: Inherent glycemic potential (IGP) is governed by unique intrinsic factors. Microstructure, dense matrix composition and interactions impede enzyme penetrance. Molecular configuration of starch limits digestibility and ultimate IGP. Comprehensive analysis of indices validated low IGP of pearl millet for first time.